Colaboração interinstitucional no Brasil: como transformar experiência em realidade? - Perret, Lívia (2011)
This research deals with the public institutional arrangement adopted by the federal government in fighting corruption. The academic approach aims to recognize the peculiarities of institutional public relations. The survey results proved to be the cooperation between public institutions arrangement suitable for overcoming the limits and scope of bureaucratic efficiency and effectiveness of public services, although there are problems in relationships and structural difficulties in punishing the bad servers. The empirical material reflects the views of civil servants who, according to the positions they hold in public administration were involved in several lawsuits of this kind. The experiences can serve as a starting point to improve the model.